A mini review of recent progress on vortex-induced vibrations of marine risers. (1st January 2020) - Liu, Guijie; Li, Haiyang; Qiu, Zhaozun; Leng, Dingxin; Li, Zhixiong; Li, Weihua
Abstract: Marine risers are subject to vortex-induced vibration (VIV) caused by a combination of various external and internal excitations. The external excitations include the current-induced hydrodynamic forces and the wave-induced motions of the floating platform, while the internal excitation refers to the effect of internal flow. With significant increase of the riser aspect ratio, the VIV becomes much more complicated, resulting in more frequent fatigue damages to the risers. Hence, VIV is an important research area in marine engineering. This review surveys the latest progress on the VIV research, including the multi-mode response, VIV response at high Reynolds numbers, flow-induced vibrations between multiple marine risers, VIV of inclined risers and intermittent VIV in oscillatory flow. Particularly, the impacts of the floating platform and internal flow that have not been widely considered in previous studies are discussed to comprehensively understand the VIV of marine risers. Moreover, typical experimental and numerical investigations on the VIV of marine risers are also introduced. Highlights: This paper reviews recent progress on VIV of marine risers in multi-mode response and response at high Reynolds numbers. This paper also reviews flow-induced vibration of multiple marine risers, VIV of the inclined riser and intermittent VIV. The impact of the floating platform and internal flow on VIV are reviewed to comprehensively understand the VIV of risers. The bottleneck of the current research is briefly explained, and the future research direction is pointed out as well.